Effects of stacking sequences on static, dynamic mechanical and thermal properties of completely biodegradable green epoxy hybrid composites. (6th September 2019) - Krishnasamy, Senthilkumar; Thiagamani, Senthil Muthu Kumar; Muthukumar, Chandrasekar; Tengsuthiwat, Jiratti; Nagarajan, Rajini; Siengchin, Suchart; Ismail, Sikiru O
Abstract: Hybrid composites reinforced with the hemp (H) and sisal (S) in various layering arrangements were fabricated, using hot press moulding technique and their properties were investigated. The flexural, impact and thermal properties of the sisal fibre reinforced composites improved significantly with the introduction of hemp in their stacking sequence. However, the hybrid composite configurations at which the optimum properties occur vary from one stacking sequence to the other. The hybrid composites with sisal in skin and hemp at core (SHHS) showed balanced mechanical properties, while the HHSS composites provided the best thermal resistance. The increased strength, stiffness and thermal stability for certain hybrid configurations indicate their suitability for structural engineering applications.